Report on existing strategies of key maritime sectors and their future development trends - Tuomas Pohjola; Anu Lähteenmäki-Uutela; Merle Kuris; Lenita Nieminen; Olena de Andres Gonzalez (Finnish Environment Institute, SYKE, 2022)
The Blue economy concept and the Blue Growth agenda as a set of strategic objectives, offer
principles and guidance to identify blue economy potential for the cross-border Maritime Spatial
Planning (MSP) processes. Coastal regions and areas are recognised as having economic growth
potential that exceeds the levels of inland regions, which indicates that the sea basin withholds
valuable strategic resources in aiming for sustainable growth in the Plan4Blue (P4B) project area in
Finland and Estonia. The P4B output report 1.1.1 presents the past and current economic
developments of the selected blue industries in the project region. This report builds on the current
state analysis to outline and summarise some key strategic visions, aims and objectives for the
future, communicated by a wide range of blue economy stakeholders in the Baltic Sea Region (BSR)
and globally, that is the EU, OECD, UN and focal blue industries that have all published visions and
guidelines or strategic objectives and policy papers to pursue future growth in a sustainable manner.
The strategies for the key blue industries call for cross-border and cross-sectoral development in the
Baltic Sea region to achieve blue growth effectively. In order to maintain and improve the health of
the Baltic Sea and wellbeing in the coastal areas requires strategic goal setting for short, medium
and long-term. The blue economy industries are interconnected and interdependent, which should be
seen as an advantage in the strategy formation and differentiation in the markets to achieve
economic growth in the future. More research is needed for more deeply understanding sustainable
blue economy dynamics and sectoral linkages within the wider regional economy.